Impacts of urbanization on West Nose Creek: a Canadian experience - van Duin, B.; Garcia, J. (Water science and technology, 2006)
The lower reaches of West Nose Creek have been subject to urbanization since the 1970s, leading to channel widening and excessive erosion. This paper discusses what would likely happen if urbanization were allowed to continue in the same manner. Comparisons are presented of the channel width and depth for both the upstream rural and downstream urbanizing reaches. Estimates of the evolution of the creek were generated by linking the dominant discharge to the entire shape and volume of the hydrograph that the creek is subjected to rather than solely considering peak discharges. Potential remedial measures and stormwater management philosophies are discussed in relationship to instream flow needs (IFNs) initiatives. IFNs are generally developed by relating the amount of suitable aquatic habitat to the quantity of flow. The emphasis has so far been on IFNs for large river systems. Unfortunately, none of the IFN approaches cover streams that are subject to significant urbanization. In urbanized streams the issue is not as much the impacts due to withdrawals but due to significantly increased runoff rates and volumes generated within the urban areas. Examples are provided how fisheries habitat is impacted by the changed hydrologic regime and changed stream morphology.